2011
DOI: 10.1007/s10570-011-9515-1
|View full text |Cite
|
Sign up to set email alerts
|

The synergetic effect of phenylphosphonic acid zinc and microfibrillated cellulose on the injection molding cycle time of PLA composites

Abstract: This study evaluates the effects of nucleants phenylphosphonic acid zinc (PPA-Zn) and talc, mold temperature, and microfibrillated cellulose (MFC) reinforcement in the acceleration of injection molding cycle of polylactic acid (PLA). PLA was dissolved in an organic solvent, mixed with nucleant and MFC, and dried compounds were injection molded into molds at temperatures ranging from 40°C to 95°C and holding times from 10 s to 120 s. Our results showed that PPA-Zn is more effective nucleating agent compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…Nevertheless, the brittleness, slow crystallization rate, and low glass transition temperature of PLA limit its usages [1,2,7,8]. Enhancing the crystallization rate and developing higher crystallinity in PLA can improve its mechanical strength and service temperature, thereby broadening its applications [2,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the brittleness, slow crystallization rate, and low glass transition temperature of PLA limit its usages [1,2,7,8]. Enhancing the crystallization rate and developing higher crystallinity in PLA can improve its mechanical strength and service temperature, thereby broadening its applications [2,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…During these processes, it is a challenge to achieve high PLA crystallinity within a very short residence time for obtaining final products with desirable properties. In injection molding process, the slow crystallization rate of PLA leads to a longer molding cycle in order to develop a crystalline molded part possessing high mechanical strength and modulus [10]. The crystallization kinetics of PLA also influences foam processes.…”
Section: Introductionmentioning
confidence: 99%
“…The tensile strength of bamboo fiber ranges between 150 and 810 MPa (Shihong et al 1994), while E-glass fiber has a high value of 3450 GPa (Katz et al 1987). Previous studies reported that micro/nano-sized bamboo fibrils (MBFs) have potential as mechanical performance enhancers in polymers and composites (Minelli et al 2010;Suryanegara et al 2011). Phong et al (2013) compared the properties of carbon fabric composites made up of neat epoxy and modified epoxy with the inclusion of MBF.…”
Section: Hybrid Compositementioning
confidence: 99%
“…MFC-reinforced polylactic acid (PLA) nanocomposites were prepared by stirring MFC in a mixture of water and acetone (Suryanegara et al, 2009;Suryanegara et al, 2011). Successive centrifugations were performed to replace water by acetone, and then acetone was replaced by dichloromethane using the same procedure.…”
Section: Solvent Mixture and Solvent Exchangementioning
confidence: 99%
“…After evaporation of the liquid (acetone and water), the mixture was kneaded with a twin rotary roller mixture. It was found that addition of 10 wt% MFC increased the stiffness of PLA at high temperatures and allowed ejection of the injected samples without distortion at a holding time of just 10 s (Suryanegara et al, 2011). The compounds were crushed into small pieces and compressed at 160°C.…”
Section: Melt Compounding Using Solvent Exchangementioning
confidence: 99%